Quasi-Bayesian model selection - Atsushi Inoue; Mototsugu Shintani (Quantitative Economics, 2019)
In this paper, we establish the consistency of the model selection criterion based on the quasi-marginal likelihood (QML) obtained from Laplace-type estimators. We consider cases in which parameters are strongly identified, weakly identified and partially identified. Our Monte Carlo results confirm our consistency results. Our proposed procedure is applied to select among New Keynesian macroeconomic models using US data.
Keywords: C11; C32; C52; 330; Impulse response function matching; Laplace-type estimators; quasi-marginal likelihood